Whole-Exome Sequencing Enables Rapid Determination of Xeroderma Pigmentosum Molecular Etiology (2013)
Xeroderma pigmentosum (XP) is a rare autosomal recessive disorder haracterized by extreme sensitivity to actinic pigmentation changes in the skin and increased incidence of skin cancer. In some cases, patients are affected by neurological alterations. XP is caused by mutations in 8 distinct genes (XPA through XPG and XPV). The XP-V (variant) subtype of the disease results from mutations in a gene (XPV, also named POLH) which encodes for Polg, a member of the Y-DNA polymerase family. Although the presence and severity of skin and neurological dysfunctions differ between XP subtypes, there are overlapping clinical features among subtypes such that the sub-type cannot be deduced from the clinical features. In this study, in order to overcome this drawback, we undertook whole-exome sequencing in two XP sibs and their father. We identified a novel homozygous nonsense mutation (c.897T.G, p.Y299X) in POLH which causes the disease. Our results demonstrate that next generation sequencing is a powerful approach to rapid determination of XP genetic etiology.